Chemical Characteristics of Biscuit Substituted by Modified Cassava Product (Mocap) Flour from High Cyanide Variety of Cassava - Harijono Harijono; Maimunah Hindun Pulungan; Jhauharotul Muchlisyiyah; Erna Triyas Tanti; Teti Estiasih (Research Journal of Life Science, 2017)
Cassava (Manihot esculenta Cranzt) is easily cultivated and an important source of carbohydrates. Currently, only a certain type of low cyanide cassava has been utilized for food product and intermediate product as flour. Processing of high cyanide cassava through submerged and solid-state fermentation simultaneously into mocap (modified cassava product) flour has successfully lowered the cyanide into a safe level for consumption. The application of mocap flour for biscuit is important to know the characteristic changes that occur due to substitution of mocap flour. Variations of wheat flour: mocap flour of 40:60, 30:70, 20:80, 10:90, and 0:100 were used in the preparation of biscuits. The resulting biscuits were analyzed for their chemical characteristics including moisture, protein, fat, starch, amylose, crude fiber, reducing sugars, and cyanide compounds. The cyanide compounds comprised of total cyanide, HCN, and cyanogenic glycosides.  Substitution of wheat flour by mocap flour in biscuit making produced the changes of biscuit characteristics. Protein, moisture, starch, amylose, fat, and reducing sugar content was decreased by increasing substitution of mocap flour. Meanwhile, crude fiber and cyanogenic compounds increased by increasing mocap flour substitution. All biscuits with variation of mocap flour substitution were safe to consume because of low level of cyanides.